2017
DOI: 10.3892/etm.2017.5516
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of caspofungin combined with trimethoprim/sulfamethoxazole as first‑line therapy to treat non‑HIV patients with severe pneumocystis pneumonia

Abstract: Abstract. Combined treatment with caspofungin and trimethoprim/sulfamethoxazole (TMP/SMZ) as salvage therapy in non-HIV positive patients with severe pneumocystis pneumonia (PCP) yields poor outcomes. It remains unknown whether the use of this combination strategy as a first-line therapy would improve patient outcomes. The present study aimed to assess the efficacy of caspofungin combined with TMP/SMZ as a first-line therapy in non-HIV positive patients with severe PCP. A retrospective cohort study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…With the increasing complexity of azole-based prophylaxis (e.g., drug-drug interactions), echinocandins have garnered attention for their potential in antifungal prophylaxis [ 38 , 39 ]. However, despite limited alternatives to standard TMP-SMX, micafungin, anidulafungin and CAS have not been recommended for prophylaxis against PCP based on in vivo efficacy [ 26 , 40 , 41 , 42 ]. The PK profile of rezafungin not only sets it apart from other echinocandins in traditional PK analysis; higher penetration of rezafungin at the infected tissue site, as observed compared with micafungin, may explain observed differences in efficacy compared with other echinocandins [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing complexity of azole-based prophylaxis (e.g., drug-drug interactions), echinocandins have garnered attention for their potential in antifungal prophylaxis [ 38 , 39 ]. However, despite limited alternatives to standard TMP-SMX, micafungin, anidulafungin and CAS have not been recommended for prophylaxis against PCP based on in vivo efficacy [ 26 , 40 , 41 , 42 ]. The PK profile of rezafungin not only sets it apart from other echinocandins in traditional PK analysis; higher penetration of rezafungin at the infected tissue site, as observed compared with micafungin, may explain observed differences in efficacy compared with other echinocandins [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports showed that after clinical failure or allergy of first‐line TMP/SMZ, most patients had their prognosis improved with second‐line therapy, which was combined with caspofungin and TMP/SMZ or other agents [15–17]. Moreover, studies focused on HIV‐negative patients with severe PCP showed that caspofungin combined with TMP/SMZ was a promising and effective first‐line therapy [18,19]. Zhang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Zhang Gensheng from Zhejiang University School of Medicine used caspofungin and coSMZ as a first-line treatment regimen for non-HIV PCP patients, and the results were similarly effective. [13] However, the primary disease of the patients in the above studies were not SLE, this study focused on the effect of combined use of caspofungin and coSMZ in patients of SLE with PCP, and hopefully, they could serve as a supplementary report to the treatment regimen. The results of this study are similar to those of the above studies, for both of them had proven that the combination of 2 drugs is effective in the treatment of PCP.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of caspofungin in the treatment of PCP has been reported both in China and abroad, the prognosis of which was better than that of coSMZ alone. [11–13] From January 2013 to December 2017, 9 patients of SLE with PCP were admitted and treated with caspofungin combined with coSMZ in Rheumatology and Immunology Department, Tangshan Gongren Hospital. The data were analyzed and reported here.…”
Section: Introductionmentioning
confidence: 99%